Overview of harmful algal blooms (red tides) in Hong Kong during 1975–2021 - Kin Chung Ho (Journal of Oceanology and Limnology, 2022)

Deep Brain Stimulation of the Interposed Nucleus Reverses Motor Deficits and Stimulates Production of Anti-inflammatory Cytokines in Ataxia Mice - Gajendra Kumar; Pallavi Asthana; Wing Ho Yung; Kin Ming Kwan; Chung Tin; Chi Him Eddie Ma (Molecular Neurobiology, 2022)

Zooplankton Population and Community Structure Changes in Response to a Harmful Algal Bloom Caused by Prorocentrum donghaiense in the East China Sea - Anglu Shen; Wenwen Chen; Yongjiu Xu; Kin-Chung Ho (Journal of Marine Science and Engineering, 2022)
Blooms of the dinoflagellate Prorocentrum donghaiense have had adverse impacts on marine ecosystems. However, ecological details, particularly the impacts and processes of the P. donghaiense bloom on the zooplankton community structure are poorly known. We investigated the changes of zooplankton communities in situ within the whole process of a P. donghaiense bloom in the coastal waters in southern Zhejiang Province, China, in May 2016. Results showed that ecological changes during the blooms of P. donghaiense could be divided into three major phases, namely the growth, maintenance, and dissipation phases with regard to the cell abundance of P. donghaiense by bottle sampling of plankton. A total of 42 species of zooplankton were identified. The average abundance and species number of zooplankton in the growth phase were significantly higher than those in the maintenance and dissipation phases. It is shown that the top-two highest proportions of zooplankton in the growth phase were small jellyfishes and copepods, while small jellyfishes and chaetognaths, and copepoda larvae and chaetognaths were the top-two highest in the maintenance and dissipation phases respectively. However, the values of biodiversity index have no statistically significant differences between the three phases. The present results suggested that P. donghaiense bloom produced significant negative impacts on the abundance and species composition of zooplankton with particular reference to copepods.